The reality of using digital stories among students with autism in the early intervention stage from the point of view of female teachers in Jeddah - Almutiri, Hala Harban (Journal of Curriculum and Teaching Methodology, 2023)
The aim of this research is to reveal the reality of using digital stories among students with disabilities in the intermediate stage from the point of view of teachers in Jeddah. The research tool was a questionnaire، while the purposes of the research were represented in a random sample of (25) parameters. The results showed that the vocabulary of the study sample strongly agreed with the reality of using the digital story among students with disabilities in the city of Jeddah، where their average agreement on the first axis was (4.29 out of 5)، which indicates that I strongly agree. And the average of the second axis was (3.75 out of 5)، which indicates I agree. The research also found that the use of digital stories among students with disabilities in the intermediate stage is an effective tool in achieving the educational goals of students with disabilities.
Keywords: digital stories; autism disorder; early intervention stage; students; Jeddah city